Baffled reactor units (BRU) for domestic wastewater treatment - Mohd. Azraai Kassim, 1958-; Zaini Ujang, Prof. Dato' Ir. Dr., 1965-; Sarifah Yaacob; National Seminar on Advances in Environmental Control Technology (1993 : Kuala Lumpur)
10